Comparison of Results of Minimal Invasive Surgery for Pilonidal Sinus with Karydakis Procedure: Less is More (Annals of Medical Research, 2021)
Aim: Controversy still remains regarding the best surgical technique to use for the treatment of pilonidal disease to minimize disease recurrence and patient discomfort. Minimal surgical procedures can be performed on an outpatient basis. In this study, the early results of our minimally invasive operative approach cases are compared with Karydakis flap reconstruction results.
Keywords: Pilonidal Sinus; Minimally Invasive Surgery; Karydakis Flap Procedure.